Radiographic findings of SARS‐CoV‐2 infection. Issue 2 (3rd March 2021) - Marco, Catherine A.; Repas, Steven J.; Studebaker, Haely; Buderer, Nancy; Burkhammer, Joseph; Shecter, Jonathan; Hinton, Amanda; Ballester, J. Michael; Angeles, John Paul; Kleeman, Benjamin
Abstract: Study objective: The 2019–20 coronavirus pandemic is caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), which causes coronavirus disease 2019 (COVID‐19). This study was undertaken to identify and compare findings of chest radiography and computed tomography among patients with SARS‐CoV‐2 infection. Methods: This retrospective study was undertaken at a tertiary care center. Eligible subjects included consecutive patients age 18 and over with documented SARS‐CoV‐2 infection between March and July 2020. The primary outcome measures were results of chest radiography and computed tomography among patients with documented SARS‐CoV‐2 infection. Results: Among 724 subjects, most were admitted to a medical floor (46.4%; N = 324) or admitted to an ICU (10.9%; N = 76). A substantial number of subjects were intubated during the emergency department visit or inpatient hospitalization (15.3%; N = 109). The majority of patients received a chest radiograph (80%; N = 579). The most common findings were normal, bilateral infiltrates, ground‐glass opacities, or unilateral infiltrate. Among 128 patients who had both chest radiography and computed tomography, there was considerable disagreement between the 2 studies (52.3%; N = 67; 95% confidence interval: 43.7% to 61.0%).). The presence of bilateral infiltrates (infiltrates or ground‐glass opacities) was associated with clinical factors including older age, ambulance arrivals, more urgent triage levels, higher heart rate, and lower oxygen saturation. Bilateral infiltrates were associated with poorer outcomes, including higher rate of intubation, greater number of inpatient days, and higher rate of death. Conclusions: Common radiographic findings of SARS‐CoV‐2 infection include infiltrates or ground‐glass opacities. There was considerable disagreement between chest radiography and computed tomography. Computed tomography was more accurate in defining the extent of involved lung parenchyma. The presence of bilateral infiltrates was associated with morbidity and mortality.